Rosa BIZARRO & Maria Alfredo MOREIRA (Org.) - Supervisão Pedagógica e Educação em Línguas. Mangualde: Edições Pedago. 2010. 170 pp. ISBN: 978-972-8980-98-6 [Recensão] - Rodrigues, Angelina (Linguarum Arena, 2018)
.